2020
DOI: 10.2298/sarh190504094s
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficiency of a sodium perborate - hydrogen peroxide mixture for intracoronal non-vital teeth bleaching

Abstract: Introduction/Objective The aim was to evaluate initial efficiency of sodium perborate (tetrahydrate) and 30% hydrogen peroxide mixture for intracoronal non-vital teeth bleaching ("walking bleach" technique). Methods Forty patients with discolored teeth were included in the study. Based on their history and clinical examination, causes of discoloration were classified as necrotic pulp, "endo-sealer" or unknown. The "walking bleach" technique was performed by applying sodium perborate (tetrahydrate) and 30% hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…An important factor in the success of the bleaching treatment is the time the discoloration occurred. A shorter time of tooth discoloration has a better prognosis of bleaching, whereas the outcome of bleaching older discolorations is uncertain and oftentimes unsuccessful due to a more complex integration of color in the dentin [ 2 ]. The results of our research are in line with these facts.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…An important factor in the success of the bleaching treatment is the time the discoloration occurred. A shorter time of tooth discoloration has a better prognosis of bleaching, whereas the outcome of bleaching older discolorations is uncertain and oftentimes unsuccessful due to a more complex integration of color in the dentin [ 2 ]. The results of our research are in line with these facts.…”
Section: Discussionmentioning
confidence: 99%
“…The bleaching agent was applied in the pulp chamber. The excess fluid was removed with dry cotton balls [ 2 , 9 , 17 ]. The teeth were then sealed with glass ionomer cement Fuji IX (GC, Japan) until the next treatment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Whilst whitening agents have noticeable effects on vital and non-vital teeth 1,[5][6][7] , their effects on resin-based composites remain unclear in terms of color differences and surface changes. Most studies have found color differences of non-discolored composites reaching or surpassing the CIEDE2000 50:50% perceptibility (∆E 00=0.81) but below the 50:50% acceptability thresholds (∆E00=1.77) [8][9][10][11] , rarely color differences were shown to exceed the 50:50% acceptability threshold 12,13) .…”
Section: Introductionmentioning
confidence: 99%